Variasi Warna Fly Grill Dan Pengaruhnya Terhadap Kepadatan Lalat Rumah (Musca domestica) - Surahma Asti Mulasari; Destri Ika Thamarina (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2022)
Garbage is something that is no longer needed, used and needed anymore. Trash that is buried and decayed will become a breeding ground for flies. The fly density level is the number of flies measured using a fly grill and can be used as a parameter to determine the success of waste management at the TPA or TPS. At the temporary disposal site on Jalan Brigjend Katamso, Yogyakarta City, there was an increase in the volume of waste and no previous measurements of fly density had been carried out. The purpose of this study was to determine differences in the density of house flies (Musca domestica) on various fly grill colors at the Temporary Disposal Site of Jalan Brigjend Katamso Yogyakarta. The type of research in this study is quantitative with an experimental analytical design using a post test only control group design approach. Based on the results of the study, there were differences in the density of house flies (Musca domestica) on red, orange, blue, purple and unpainted fly grills in temporary shelters on Brigjend Katamso Street, Yogyakarta City with the highest density of house flies (Musca domestica) on fly the red grille with an average value of 10 and the lowest average on the blue fly grill with an average value of 3.4. There is a significant difference between the red fly grill and the blue fly grill with a significance value of 0.041 < 0.05. Based on the results of the study, it can be concluded that the red fly grill is the preferred color for flies with the highest fly density level and the blue fly grill is the disliked color for flies with the lowest fly density level.